Pelatihan Laporan Keuangan sebagai Strategi Peningkatan Keberlanjutan UMKM Catering di Tangerang Selatan: Financial Report Training as a Strategy to Improve the Sustainability of Catering MSMEs in South Tangerang - Daurrohmah, Eka Wirajuang; Robiansyah, Anton; Wisnantiasri, Sila Ninin; Paramitha, Diky; Dwirini, Dwirini (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Micro, Small, and Medium Enterprises (MSMEs) face major challenges in financial management, especially in preparing financial reports. A community service program was conducted at the South Tangerang Catering MSME Community to improve participants' ability to prepare simple financial reports. This activity includes theoretical and practical training, intensive mentoring, and evaluation through observation and questionnaires. The results showed that 90% of participants felt more confident in preparing financial reports, and most were able to produce profit and loss reports, balance sheets, and cash flow independently. Mentoring has proven effective in helping participants separate personal and business finances. This program has succeeded in improving participants' financial literacy while supporting the sustainability of MSME businesses.